On the value distribution of two Dirichlet L-functions over sums of two zeros of the Riemann zeta-function - Maugmai, Nattiwut; Srichan, Teerapat (Progress in Applied Science and Technology, 2020)
Let and denote the non-trivial zeros of the Riemann zeta-function with 0" src="https://latex.codecogs.com/gif.latex?γ&space;,γ&space;’>&space;0"> and . Under the assumption of the Riemann Hypothesis, we show that for a positive proportion of , the values of the Dirichlet -function and associated with the primitive characters and to different prime moduli are linearly independent over .